The Tax Management Strategy for Enhancing the Efficiency of the Tax Burden at PT XYZ - Akbar, Abdul Azhim; Sari, Septy Dwi Indah; Pahala, Indra; Wahono, Puji (The Future of Education Journal, 2025)
Taxes are a primary source of state revenue but, on the other hand, can be a burden for companies as they reduce net profit. Therefore, an appropriate tax management strategy is needed to legally minimize the tax burden. This study aims to analyze the tax planning strategies implemented by PT XYZ, a company engaged in human resource solutions. This research employs a qualitative approach through interview techniques to obtain relevant data. The results show that PT XYZ has applied various tax planning strategies, including: deferring revenue recognition for projects that are not yet substantially completed, accurate and complete documentation of tax withholdings, careful management of input and output VAT, grouping non-deductible expenses to avoid tax corrections, optimizing the recognition of deductible expenses, and using the services of tax consultants. All these strategies are carried out in compliance with the prevailing tax regulations in Indonesia, thereby not only reducing the company’s tax burden but also improving its tax compliance.